Evaluation of a mechanized CTL harvesting system in different geometric thinning operations in terms of productivity, cost, biomass conversion, residual stand damage and spacing uniformity - Makoto, Munyaradzi (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScFor)--Stellenbosch University, 2021.